2021
DOI: 10.3389/fcvm.2021.637021
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Dobesilate (CaD) Attenuates High Glucose and High Lipid-Induced Impairment of Sarcoplasmic Reticulum Calcium Handling in Cardiomyocytes

Abstract: Calcium dobesilate (CaD) is used effectively in patients with diabetic microvascular disorder, retinopathy, and nephropathy. Here we sought to determine whether it has an effect on cardiomyocytes calcium mishandling that is characteristic of diabetic cardiomyopathy. Cardiomyocytes were sterile isolated and cultured from 1 to 3 days neonatal rats and treated with vehicle (Control), 25 mM glucose+300 μM Palmitic acid (HG+PA), 100 μM CaD (CaD), or HG+PA+CaD to test the effects on calcium signaling (Ca2+ sparks, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…It can also protect the endoplasmic reticulum and mitochondria and reduce excessive calcium loading, as reflected in a decrease in endothelial cell damage [260]. Deng and colleagues [258] also confirmed that dobesylate reduced endoplasmic reticulum calcium impairment in cultured rat cardiomyocytes at both high glucose and lipid levels. Its anti-glycation and anti-AGEs potential (higher than metformin) was confirmed in vitro in a model with bovine serum albumin and MGO.…”
Section: Peripheral Vasodilators and Vasoprotectivesmentioning
confidence: 99%
“…It can also protect the endoplasmic reticulum and mitochondria and reduce excessive calcium loading, as reflected in a decrease in endothelial cell damage [260]. Deng and colleagues [258] also confirmed that dobesylate reduced endoplasmic reticulum calcium impairment in cultured rat cardiomyocytes at both high glucose and lipid levels. Its anti-glycation and anti-AGEs potential (higher than metformin) was confirmed in vitro in a model with bovine serum albumin and MGO.…”
Section: Peripheral Vasodilators and Vasoprotectivesmentioning
confidence: 99%